The role of classroom- and individual-level teen stereotypes in Chinese adolescents' academic adjustment: A multilevel analysis - Qu, Yang; Devakonda, Varun; Shi, Zeyi; Yang, Beiming; Wang, Qian (Frontiers in Psychology, 2022)
Adolescence is often portrayed in a negative light in Western culture, with teens being viewed as rebellious and irresponsible. Yet, there is substantial cultural and individual variability in views of teens. The empirical research to date is limited in that it mainly examines whether teen stereotypes are influential at the individual level. Teen stereotypes might also be perpetuated at the classroom level, which may have important implications for adolescent adjustment over time. Focusing on adolescents in Chinese culture where the teen years are often viewed in a positive light, this two-wave longitudinal study employed multi-level analyses to investigate whether stereotypes of adolescence at the classroom level play a role in Chinese adolescents’ academic adjustment over time (N = 785; 55% girls; mean age = 12.96 years). Consistent with prior research on views of teens, the present analyses suggested that teen stereotypes regarding family obligation and school engagement at the individual level predicted adolescents’ value of school and self-regulated learning strategies over the seventh grade. More importantly, classroom-level teen stereotypes were also largely predictive of adolescents’ value of school and self-regulated learning strategies over time, controlling for their earlier academic adjustment, individual-level teen stereotypes, and classroom-level adjustment. Taken together, these findings indicate that stereotypes of adolescence in classroom or peer settings may contribute to adolescents’ academic adjustment during this phase. The findings also provide a potential foundation for interventions aimed at promoting adolescents’ positive development via changing teen stereotypes in the classroom.